EFEITOS DA PLUVIOSIDADE E VOLUME DE NINHOS ABANDONADOS DE CUPINS Constrictotermes cyphergaster (Silvestri, 1901) (INSECTA BLATTODEA) NA DIVERSIDADE DE ARANHAS (ARACHNIDA: ARANEAE) NA CHAPADA DO ARARIPE, BRASIL - Azevedo, Raul; Azevedo, Francisco Roberto de; Saporetti Junior, Amilcar Walter; Souza, Adriano Medeiros De (Revista Nordestina de Zoologia, 2020)
The present study describes the use of abandoned termite nest by spiders. Sixty abandoned Constrictotermes cyphergaster (Silvestri, 1901) were sampled and dissecated which resident spiders were collected. A total of 132 adults individuals belonged to 19 species/morphospecies were sampled. Ibotyporanga sp. (Pholcidae) was the most abundant morphospecies and increased their occurence on nest sampled on dry month. In despite of the observed rainfall effects on species richness and spider abundance, it was not observed any difference on spider species composition on abandoned nest between wet and dry month due species cluster without distinction also non significative similarity. It was not observed nest volume effect on species richness or spider abundance. Therefore, due the cluster of the fauna be composed by a only unique non distinct group, the data suggest that C. cyphergaster nest protect resident spiders species against change effects on temperature and humid based on rainfall occurence.